The Impact of Energy Market Uncertainty Shocks on Energy Transition in Europe - Balcilar, Mehmet; Roubaud, David; Shahbaz, Muhammad (Sage Publications Inc, 2019)
We study effects of energy market uncertainty shocks on energy transition on the 28 European Union countries from 1990 to 2015 using annual frequency data. We assess the effects of oil price as well as the energy market supply, demand, and residual price shocks using a time-varying parameter panel data stochastic volatility model. We show the importance of reducing energy market uncertainty for the success of a clean energy transition in Europe as uncertainties have strong time-varying effects on the transition from fossil fuels to renewable energy. The oil price and residual energy price uncertainties are the key factors encouraging renewable energy transition that reduces the vulnerability of economies to energy shocks. Energy supply shocks affect the transition negatively while the demand shocks work similarly to residual energy prices shocks, requiring a robust energy base that is less volatile. The paper also discusses policy recommendations.
Keywords: Energy transition; Uncertainty; Europe; Stochastic volatility